Mapping knowledge-to-action processes in the implementation of trauma-sensitive sport programming in a national youth organization - Shaikh, Majidullah; Forneris, Tanya (Université d'Ottawa | University of Ottawa, 2021)
Background. Youth program staff’s use of trauma-sensitive sport practices (TSSP) can help children who have faced significant adversities the opportunities to practice self-regulation, perceive safety and control, build supportive adult-child and peer relationships, and experience healthy psychological escape through sport; such opportunities can contribute to these children’s resilience-building and well-being. This dissertation explored the translation of TSSP in a national youth-serving community organization. Twelve staff from three sites participated in the pilot stage, which involved a training intervention led by TSSP-experts (multiple-day workshop and monthly consultations), and delivery of TSSP-programming to child members ages 9-12. In the expansion stage, these staff took on master trainer roles to train 20 new staff, who then implemented TSSP-programming across an additional 12 sites. Methods. In this mixed-methods multiple case study, the knowledge-to-action cycle (Graham et al., 2006) was used to guide the exploration of TSSP-translation. The studies reflected five phases of this cycle: (a) adapt knowledge to the local context, (b) assess barriers and facilitators to knowledge use, (c) select, tailor, and implement intervention, (d) monitor knowledge use, and (e) evaluate outcomes. Data were gathered throughout, using semi-structured interviews, focus groups, and self-report questionnaires with staff and members; staff-completed session logbooks; observations of training, program delivery, and debriefing sessions; and online communications. Results. Study 1 examined the process of adapting the TSSP to the organization’s context and assessing the strengths and challenges of TSSP-use during the pilot stage. Here, staff found that TSSP training workshops and ongoing consultations were useful and applicable to practice, and that TSSP aligned and/or enhanced their existing youth work; challenges were recognized in limited member recruitment, staff turnover, and behavioural challenges. Adaptations were made to improve recruitment and staff retention strategies, and tailoring training to meet staff’s needs. Study 2 explored the learning experiences of expansion staff from participating in the adapted TSSP training intervention. Here, the training was effective in improving knowledge and attitudes of staff on TSSP, however the unstructured ongoing consultations were not always conducive to enhancing learning. Study 3 monitored how TSSP-knowledge is applied by expansion staff in their contexts. Here, observations revealed that all clubs were capacitated in delivering basic TSSP components (e.g., facilitating psychological safety, caring relationships). Trained staff were essential for implementing high-quality TSSP, and staff turnover posed challenges to maintaining this quality. Study 4 evaluated the outcomes of staff’s TSSP-use. Here, staff reported that members were growing in their abilities to participate willingly, self-regulate, and build positive relationships; staff also reported challenges in some members’ development given self-esteem/confidence issues, and dysregulated or disruptive behaviours. Discussion/Conclusions. The results of these studies point to: (a) how a KT lens can be used to guide evaluation of the implementation processes, (b) the value of rolling out interventions using a developmental approach (small steps over time), (c) using ongoing evaluation to adapt programming to meet stakeholders’ needs, (d) the effectiveness of leaders TSSP-use on children’s outcomes; and (e) the existing capacities, strengths, and challenges to implementing quality practices in under-resourced community contexts.
Keywords: community-engaged; youth; knowledge mobilization; children